2020
DOI: 10.1111/gcb.15253
|View full text |Cite
|
Sign up to set email alerts
|

Caribbean reefs of the Anthropocene: Variance in ecosystem metrics indicates bright spots on coral depauperate reefs

Abstract: Human activities in the Anthropocene are altering ecosystems, causing significant differences from their predecessors in species composition, community structure, and ecological function. Examples of such altered ecosystems include regenerating forests dominated by non-native trees, grassland, and shrubland systems replacing forests due to human alteration of fire regimes, and the ongoing tropicalization of temperate marine ecosystems (Hobbs et al., 2006; Vergés et al., 2014). Some ecosystem changes are so dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 76 publications
1
35
1
Order By: Relevance
“…6a), a finding consistent with prior reports that coral and macroalgae compete with each other (Arnold, Steneck, and Mumby, 2010;Box and Mumby, 2007;Foster, Box, and Mumby, 2008;Jackson et al, 2014;Thurber et al, 2012). In fact, the data from Figure 6a could be superimposed on those of Figure S4 from Lester et al (2020) regressing percent macroalgae cover on percent coral cover from 328 sites across the Caribbean from AGGRA surveys. Previous studies also have reported that areas with Diadema present were associated with areas of greater coral cover (Carpenter and Edmunds, 2006;Edmunds and Carpenter, 2001;Idjadi, Haring, and Precht, 2010), and like Bodmer et al (2015) my results revealed that sea urchin density was positively correlated with percent coral cover (Fig.…”
Section: Significance Of Sea Urchinssupporting
confidence: 86%
“…6a), a finding consistent with prior reports that coral and macroalgae compete with each other (Arnold, Steneck, and Mumby, 2010;Box and Mumby, 2007;Foster, Box, and Mumby, 2008;Jackson et al, 2014;Thurber et al, 2012). In fact, the data from Figure 6a could be superimposed on those of Figure S4 from Lester et al (2020) regressing percent macroalgae cover on percent coral cover from 328 sites across the Caribbean from AGGRA surveys. Previous studies also have reported that areas with Diadema present were associated with areas of greater coral cover (Carpenter and Edmunds, 2006;Edmunds and Carpenter, 2001;Idjadi, Haring, and Precht, 2010), and like Bodmer et al (2015) my results revealed that sea urchin density was positively correlated with percent coral cover (Fig.…”
Section: Significance Of Sea Urchinssupporting
confidence: 86%
“…As coral reef communities change and reorganise in response to the increasing anthropogenic and climate disturbances, approaches that detect the new species configurations and their contribution to key ecosystem processes are required (Lester et al 2020;Pombo-Ayora et al 2020). Here, we show that the use of major categories (family level or above) in studying coral reef communities fails to identify strikingly distinct regimes.…”
Section: Discussionmentioning
confidence: 87%
“…For example, decreases in structural complexity and the associated loss of habitat structure have been associated with a decline in fish biomass and therefore fisheries (Rogers et al 2014). However, as shown recently in some Caribbean reefs, not all communities with low-coral cover might display compromised ecosystem functioning (Lester et al 2020), highlighting the need to understand the composition but also functioning of different coral reef communities. The use of trait-based approaches to gain insights into the role of biodiversity in ecosystem functioning has been successfully implemented to study and detect changes in fish and scleractinian coral communities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, decreases in structural complexity and the associated loss of habitat structure have been associated with a decline in fish biomass and therefore fisheries 16 . However, as shown recently in some Caribbean reefs, not all communities with low-coral cover might display compromised ecosystem functioning 42 , highlighting the need to understand the composition but also functioning of different coral reef communities. The use of trait-based approaches to gain insights into the role of biodiversity in ecosystem functioning has been successfully implemented to study and detect changes in fish and scleractinian coral communities 26 , 29 , but to date such approaches have not yet been implemented to study coral reef benthic changes beyond scleractinian corals.…”
Section: Discussionmentioning
confidence: 90%
“…As coral reef communities change and reorganise in response to increasing anthropogenic and climate disturbances, approaches that detect new species configurations and their contribution to key ecosystem processes are required 42 , 43 . Here, we selected reefs with different natural characteristics and exposed to anthropogenic factors, which we hypothesised would display different fish and/or benthic regimes, to compare the use of different biodiversity approaches.…”
Section: Discussionmentioning
confidence: 99%